A new energy based highly stressed volume concept to investigate the notch-pores interaction in thick-walled ductile cast iron subjected to uniaxial fatigue. (April 2023) - Pedranz, M.; Fontanari, V.; Raghavendra, S.; Santus, C.; Zanini, F.; Carmignato, S.; Lusuardi, D.; Berto, F.; Benedetti, M.
Graphical abstract: Highlights: Defects analyses based on CT scans to investigate fatigue damage in ductile cast iron. Plain fatigue strength controlled by shrinkage porosity in pearlitic DCI. Inverse search based on two notched geometries to derive intrinsic fatigue properties. Notch-pore interaction modeled via finite element analysis. Extreme value statistics combined with strain energy density to assess notch fatigue. Abstract: Fatigue failure of thick-walled pearlitic ductile cast iron is triggered by large shrinkage pores in plain specimens and by graphite nodules at the notch tip in severely notched specimens. These phenomena are interpreted in terms of highly stressed volume, whose definition is affected by a certain degree of arbitrariness. In the present study, a novel framework to determine the highly stressed volume is proposed. This method uses in combination the extreme value statistics and the strain energy density approach to assess the uniaxial fatigue behavior of V-notched specimens. The proposed approach will be called Energy Based Highly Stressed Volume (EB-HSV) concept.